2007
DOI: 10.1590/s0101-81752007000400012
|View full text |Cite
|
Sign up to set email alerts
|

The diet of Scinax angrensis (Lutz) tadpoles in an area of the Atlantic Forest (Mangaratiba, Rio de Janeiro) (Amphibia, Anura, Hylidae)

Abstract: Scinax angrensis (Lutz, 1973) is an endemic species, which occurs in low altitude hillside forests, distributed from the municipalities of Mangaratiba to Parati in the south of the state of Rio de Janeiro, Brazil. The aim of this study was to compare the morphology of S. angrensis tadpoles in two different stages of development, and verify their feeding spectrum. The mouth morphology of the two stages studied (27 and 37) appeared similar, with a difference in the size of the oral opening as well as an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
0
11
0
5
Order By: Relevance
“…The presence of fungi in the diet of tadpoles is also rarely reported in literature even though it is an important component in oligotrophic habitats (Altig et al 2007). Studies that address the importance of fungi in the diet of tadpoles were not found, however, Rossa-Feres et al Pfennig et al 2006;Sousa Filho et al 2007;Wickramasinghe et al 2007), and were usually associated with the diet of tadpoles in the later stages of development, unlike the three species of this study, which were in the early stages of development. The high nutritional value of invertebrates in terms of protein and energy is worthy of note (Bowen et al 1995).…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…The presence of fungi in the diet of tadpoles is also rarely reported in literature even though it is an important component in oligotrophic habitats (Altig et al 2007). Studies that address the importance of fungi in the diet of tadpoles were not found, however, Rossa-Feres et al Pfennig et al 2006;Sousa Filho et al 2007;Wickramasinghe et al 2007), and were usually associated with the diet of tadpoles in the later stages of development, unlike the three species of this study, which were in the early stages of development. The high nutritional value of invertebrates in terms of protein and energy is worthy of note (Bowen et al 1995).…”
Section: Discussionmentioning
confidence: 48%
“…A high diversity and abundance of algae is usual in tadpoles of different anuran species (Dutra & Callisto 2005;Sousa Filho et al 2007). However, the ingestion of a large amount of algae by anuran larvae will not necessarily result in nutritional gain (Pryor 2003;Akers et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heyer 1973). On the other hand, feeding behavior of tadpoles may be partially coupled with morphology and microhabitat distribution resulting in differences in diet composition, which contribute with food partitioning (Inger 1986, Rossa-Feres et al 2004, Escheverría et al 2007, Souza Filho et al 2007.…”
Section: Food Resource Partitioningmentioning
confidence: 99%
“…Conocer de qué se alimentan los renacuajos permite comprender las interacciones bióticas y abióticas que ocurren en el ecotono entre las zonas terrestres y acuáticas; así como entender la estructura trófica a escala local lo que revela los enlaces entre comunidades. Estos estudios también permiten entender el grado de susceptibilidad de las diferentes especies de anuros debido a los cambios ambientales (De Sousa et al, 2007). Desde luego permiten determinar si existe o no selección de elementos alimenticios exclusivos que satisfagan las necesidades nutricionales de los renacuajos para poder llevar a cabo la metamorfosis.…”
Section: Introductionunclassified